NAD+-dependent synthesis of a 5′-phospho-ADP-ribosylated RNA/DNA cap by RNA 2′-phosphotransferase Tpt1. Issue 18 (8th September 2018) - Munir, Annum; Banerjee, Ankan; Shuman, Stewart
Abstract: RNA 2′-phosphotransferase Tpt1 converts an internal RNA 2′-monophosphate to a 2′-OH via a two-step NAD + -dependent mechanism in which: (i) the 2′-phosphate attacks the C1″ of NAD + to expel nicotinamide and form a 2′-phospho-ADP-ribosylated RNA intermediate; and (ii) the ADP-ribose O2″ attacks the phosphate of the RNA 2′-phospho-ADPR intermediate to expel the RNA 2′-OH and generate ADP-ribose 1″–2″ cyclic phosphate. Tpt1 is an essential component of the fungal tRNA splicing pathway that generates a unique 2′-PO4, 3′-5′ phosphodiester splice junction during tRNA ligation. The wide distribution of Tpt1 enzymes in taxa that have no fungal-type RNA ligase raises the prospect that Tpt1 might catalyze reactions other than RNA 2′-phosphate removal. A survey of Tpt1 enzymes from diverse sources reveals that whereas all of the Tpt1 enzymes are capable of NAD + -dependent conversion of an internal RNA 2′-PO4 to a 2′-OH (the canonical Tpt1 reaction), a subset of Tpt1 enzymes also catalyzed NAD + -dependent ADP-ribosylation of an RNA or DNA 5′-monophosphate terminus. Aeropyrum pernix Tpt1 (ApeTpt1) is particularly adept in this respect. One-step synthesis of a 5′-phospho-ADP-ribosylated cap structure by ApeTpt1 (with no subsequent 5′-phosphotransferase step) extends the repertoire of the Tpt1 enzyme family and the catalogue of ADP-ribosylation reactions involving nucleic acid acceptors.